Membumikan Konsep Etika Islam Abdurrahman Wahid dalam Mengatasi Problematika Kelompok Minoritas di Indonesia - Muhammad Mahfud (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
Abdurrahman Wahid was one of the pioneers realization of Islamic ethical values, although it was believed to be counter-productive. He has transformative thinking in interpreting Islamic teachings especially promoting Islamic social ethics. There are three main driving factors dominating minorities; misunderstanding of Indonesia which is a democratic country, the essence of the values ??of Islamic teachings, and not yet understanding the importance of awareness of grounding Islamic ethics that is transformed into the social realm. Form of minority domination in Indonesia, among others; violence experienced by minority groups in Sampang who are Syi’ah who are considered to damage the majority of Islamic teachings, and others. There are three strategies to ground Islamic ethics in order to overcome the problems of minorities in Indonesia; transformation of Islamic ethical values ??in the social domain; the implementation of Islamic ethical values ??in overcoming the problems of minority groups, the value of love for peace, the value of upholding justice, the value of equality of human position in the eyes of law and the state, and the value of social care, and the orientation of the development of Islamic ethics must be directed towards the welfare of the people.